On the Creation of the Multimedia Project “The Memory of a Settlement”, Dedicated to the Genealogy, Oral History, and Photographic Archives of Yupik Families from the Settlement of Novoe Chaplino, Chukotka (Research Note) - Oparin, Dmitriy (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2021)
In 2020, I started a project that involved scanning and digitizing the Yupik genealogical charts compiled in Novoe Chaplino (Providensky District, coastal Chukotka) by the ethnographer Mikhail Chlenov in the 1970s and 1980s. He had assembled these materials on the basis of information from local archives and registry offices along with information obtained from communication with the elderly Yupik of Novoe Chaplino, many of whom had been born at the beginning of the 20th century. While working on the genealogical charts, I also began to collect the old photographs and documents of local residents and write down their memories of their ancestors. This is how the multimedia project came about, which presents 47 genealogical charts referring to nine Yupik clans and several hundred private photographs and documents of the inhabitants of Soviet Novoe Chaplino, as well as recollections of 77 ancestors of those Yupik living today.